EVALUATION OF TALENT MANAGEMENT AT PT. PERTAMINA GAS NIAGA MEDAN, NORTH SUMATERA - Astrid Herera Magdalena Sipayung; Prihatin Lumbanraja; Nazaruddin (RADJA PUBLIKA, 2023)
The conclusions that can be obtained based on the research studies that have been carried out are as follows: The talent management process that has been carried out has been carried out by human resource management in recruitment and selection, as well as the performance management process. Employees are grouped into a talent pool based on the leadership, fundamental and technical competencies possessed by each employee. The factor in talent management that causes decreased productivity is in the formation of competencies needed by new employees in the regeneration process. Several actions have been taken by management but need some improvement, especially in terms of recruitment and selection, performance management, orientation process, and education and training. The follow-up plans that can be carried out to overcome these problems are: Organizational preparation of talent management, from the appointment of coaches, appraisers, superiors, and the mechanism, Talent management processes that can be accessed by each employee so that assessments, strengths and weaknesses can be evaluated. This will form a self-assessment of employees, Since training needs differ between employees, the training system needs to be carried out in a participatory manner, meaning that employees register according to their training needs. This will also lead to cost efficiency in training.